The Gender Gap in Attitudes toward Capital Punishment and Life without Parole (LWOP) in Kentucky - Vito, Anthony G. (Women & criminal justice, 2025)
Over years of U.S. polls, women have consistently opposed capital punishment—especially in comparison to the attitudes of males. In addition, there has been a shift in the United States away from using the death penalty in cases of murder and toward using the long-term, open-ended, and often permanent confinement provided by the sentence of life without parole among all U.S. respondents. Using data from a poll of a representative sample of Kentucky residents conducted by the University of Kentucky’s Survey Research Center from March 4 to April 30, 2016, this study compares the attitudes of females and males concerning both capital punishment and life without parole to determine if a “gender gap” exists.